2022
DOI: 10.1029/2022jd036713
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivities of Cross‐Tropopause Transport in Midlatitude Overshooting Convection to the Lower Stratosphere Environment

Abstract: Tropopause‐overshooting convection in the midlatitudes rapidly transports lower troposphere air and cloud material to the upper troposphere and lower stratosphere (UTLS), with notable events resulting in the formation of above‐anvil cirrus plumes (AACPs). However, there is limited understanding of how transport driven by overshooting convection and AACP properties are modified by variations in UTLS environments, especially the extent of stratosphere‐to‐troposphere (i.e., downward) transport. Here, AACP develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 56 publications
2
17
0
Order By: Relevance
“…For land‐based convection, where vertical velocities are stronger and turbulence is presumably enhanced, larger fractions of environmental air will be entrained into the plume. For cases where there is strong shear at the tropopause (Gordon & Homeyer, 2022), this entrainment will be even stronger. A refinement of the method would entail trying to incorporate these effects by having mixing vary according to convective strength (e.g., land vs. ocean) and vertical shear.…”
Section: Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…For land‐based convection, where vertical velocities are stronger and turbulence is presumably enhanced, larger fractions of environmental air will be entrained into the plume. For cases where there is strong shear at the tropopause (Gordon & Homeyer, 2022), this entrainment will be even stronger. A refinement of the method would entail trying to incorporate these effects by having mixing vary according to convective strength (e.g., land vs. ocean) and vertical shear.…”
Section: Approachmentioning
confidence: 99%
“…For land-based convection, where vertical velocities are stronger and turbulence is presumably enhanced, larger fractions of environmental air will be entrained into the plume. For cases where there is strong shear at the tropopause (Gordon & Homeyer, 2022), this entrainment will be even stronger.…”
Section: Evaluating Cloud Top Altitudes and Potential Temperatures Us...mentioning
confidence: 99%
“…The smaller water vapor mixing ratio in the higher‐altitude moistening segments could also be limited to the strength of wind shear (Figure S3 in Supporting Information ) in our GEM simulation. Previous studies have shown that when the storm‐relative wind in the stratosphere is stronger, hydraulic jump occurs and AACP is produced, so a larger amount of water vapor is transported to higher altitudes (Gordon & Homeyer, 2022; Homeyer et al., 2017; O’Neill et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…(2017). Since convective moistening can be produced by storms both with and without AACPs (Gordon & Homeyer, 2022; Homeyer et al., 2017; O’Neill et al., 2021), we analyze the water vapor plume regardless of the existence of the AACP. H2normalO_normalanormalnnormalonormalmnormalanormallnormaly(t,z,normallnormalanormaltnormalinormaltnormalunormaldnormale,normallnormalonormalnnormalgnormalinormaltnormalunormaldnormale)=H2normalO(t,z,normallnormalanormaltnormalinormaltnormalunormaldnormale,normallnormalonormalnnormalgnormalinormaltnormalunormaldnormale)trueH2normalO0(t0,z,normallnormalanormaltnormalinormaltnormalunormaldnormale) ${{\mathrm{H}}_{2}\mathrm{O}\_\mathrm{a}\mathrm{n}\mathrm{o}\mathrm{m}\mathrm{a}\mathrm{l}\mathrm{y}(t,z,\mathrm{l}\mathrm{a}\mathrm{t}\mathrm{i}\mathrm{t}\mathrm{u}\mathrm{d}\mathrm{e},\mathrm{l}\mathrm{o}\mathrm{n}\mathrm{g}\mathrm{i}\mathrm{t}\mathrm{u}\mathrm{d}\mathrm{e})={\mathrm{H}}_{2}\mathrm{O}(t,z,\mathrm{l}\mathrm{a}\mathrm{t}\mathrm{i}\mathrm{t}\mathrm{u}\mathrm{d}\mathrm{e},\mathrm{l}\mathrm{o}\mathrm{n}\mathrm{g}\mathrm{i}\mathrm{t}\mathrm{u}\mathrm{d}\mathrm{e})-\overline{{\mathrm{H}}_{2}\mathrm{O}}}_{0}(t0,z,\mathrm{l}\mathrm{a}\mathrm{t}\mathrm{i}\mathrm{t}\mathrm{u}\mathrm{d}\mathrm{e})$ …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation